2014
DOI: 10.1016/j.proche.2014.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Study of Aqueous Chemical Forms of Silicon in Organic-rich Waters

Abstract: The study of silicon species in organic-rich waters is a very significant problem. This type of waters is widely spread all over the world. It is characterized by a high content of humic substances, high color of water and low pH. In this regard, a certain determination of silicon concentration in this type of waters is impossible without a preliminary investigation of silicon species. The aim of this research is therefore an investigation of the ratio of silicon dissolved forms in organic-rich waters dependin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The fulvic acid concentrations decrease with an increase in pH. The behavior of soluble humic acid is practically independent of geochemical parameters of the aquatic environment [33,34]. The redox conditions are characterized by values Eh −68 to 347 mV.…”
Section: General Characteristics Of Watersmentioning
confidence: 99%
“…The fulvic acid concentrations decrease with an increase in pH. The behavior of soluble humic acid is practically independent of geochemical parameters of the aquatic environment [33,34]. The redox conditions are characterized by values Eh −68 to 347 mV.…”
Section: General Characteristics Of Watersmentioning
confidence: 99%
“…Pokrovski and Schott (1998) reported that Si formed weak complexes in solution with simple organic ligands having carboxylic or phenolic functional groups. Kambalina et al (2014), however, concluded after spectrophotometric measurements that Si does not form stable complexes with fulvic and humic acids in weak-acid media (рН 3-4).…”
Section: Introductionmentioning
confidence: 99%
“…6 These compounds, however, are generally not very soluble and have a low bioavailability. 7 In the liquid phase, dissolved Si is mainly in the form of monosilicic acid (H 4 SiO 4 ), which is the dominant hydroxylated Si species in aqueous solutions between pH 2 and pH 9.8. 8 When the concentration of dissolved Si in aqueous solution exceeds z10 À3 mol L À1 , polymerization of Si can occur in very varied forms depending on the species and nanoparticles particles present in solution.…”
Section: Introductionmentioning
confidence: 99%